EP313/#490 Validation of mutation analysis of ovarian cancer predisposition genes in tumor tissue. (4th December 2022) - Koole, Wouter; Jansen, Anne; Ausems, Margreet; Jonges, Trudy; Witteveen, Petronella; Zweemer, Ronald; Leng, Wendy De
Abstract : Objectives: Almost 10% of ovarian cancer (OC) patients carry a somatic pathogenic variant (PV) in one of the ovarian cancer (OC) predisposition genes (e.g. BRCA1/2) and might respond to PARP inhibition. Without somatic testing these patients are denied effective treatment. Methods: To implement tumor testing of ovarian cancer predisposition genes the 523 gene panel (TSO500, Illumina) was validated in a cohort of 48 formalin-fixed paraffin-embedded archival samples with known mutation status. Blind data analysis was performed for mutational status using Franklin Genoox software (Franklin) and an in-house built Copy Number Variation (CNV) analysis. BRCA1 MLPA analysis was performed for all mutation negative samples. Results: The validation cohort consisted of ovarian (n=40), breast (n=6) and pancreas (n=2) samples of which 44 were known to contain a germline mutation and 3 a somatic mutation. After blinded data analysis, a PV was detected in 35 cases (BRCA1/2, BRIP1, RAD51C) and a variant of unknown significance in 6 cases (BRCA1/2, BRIP1, RAD51D). Exon deletions in BRCA1 were detected in 5 cases. The known molecular defect was identified in 46/48 (96%). Two CNVs (4%) were missed, a tandem duplication inclusing CHEK2 and loss of RAD51D. Conclusions: TSO500 mutation analysis can be reliably used to detect PVs in OC predisposition genes, however, CNV analysis remains challenging. Therefore, the tumor first workflow where the tumor test is performed first to guide treatment might not identify all carriers of a germline PV. However, with Dutch nationwide implementation, this universal workflow leads to genetic testing of a higher proportion of OC patients.